Effect of Gibberellic Acid (GA3) on Yield and Fruit Quality of Table Grape var. Himrod in Kathmandu Valley, Nepal (Journal of Agriculture and Environment, 2022)
The experiment was conducted at Warm Temperate Horticulture Center, Kirtipur, Kathmandu, Nepal with an aim to improve the yield and fruit quality of seedless table grape var. Himrod. Different treatments of GA3 (0 ppm,10 ppm, 20 ppm, 30 ppm, 40 ppm) were applied for two times on grape bunches after berry set. The quantitative and qualitative attributes of bunch and berry were recorded. Berry size, berry weight, berry volume, bunch weight and berry color were improved significantly in GA3 treated grape bunches whereas TA was significantly decreased. The effect of GA3 on berry diameter had significant impact on berry weight and berry volume, and thus in yield. As the yield of a vine is the product of bunch number and bunch weight, GA3 influenced the current season bunch weight by improving the berry attributes, and also affected quality attributes of grape berries in var. Himrod.